Vasa vasorum and atherosclerosis – Quid novi? - Langheinrich, Alexander C.; Kampschulte, Marian; Buch, Thomas; Bohle, Rainer M. (Thrombosis and Haemostasis, 2007)
The role of vasa vasorum (VV) in atherosclerosis is hotly debated, and new experimental techniques have recently opened an opportunity to take a fresh look at this important topic. Although the proliferation of VV due to atherogenic stimuli is controversial, experimental and clinical evidence strongly suggest the potential of VV in vascular proliferative disorders. In the past, paradigms of atherosclerosis and restenosis have excluded the adventitia and VV in the artery wall due, in part, to a lack of i) appropriate animal models featuring adventitial VV neovascularization, ii) imaging technologies to quantitate adventitial VV and plaque neovascularization and iii) its consequences, concerning information on detectable plaque substrate in vulnerable lesions. VV proliferation is associated with increasing plaque burden and is linked to cellular processes which are critical during the development of atherosclerotic plaques such as inflammation, plaque perfusion and concomitant intraplaque hemorrhage – but the regulation and induction of VV based on pathological settings are poorly understood. This review discusses the current scientific status and its controversies and identifies open research questions.
Keywords: Vasa vasorum; inflammation; atherosclerosis; intraplaque hemorrhage